The Relationship between the Physical Activity Environment, Nature Relatedness, Anxiety, and the Psychological Well-being Benefits of Regular Exercisers - Lawton, Emma; Brymer, Eric; Clough, Peter; Denovan, Andrew (Frontiers in Psychology, 2017)
Research from a variety of scientific fields suggests that physical activity in nature and feelings of connection to nature enhance psychological health and wellbeing. This study investigated the psychological health and wellbeing impact of the physical activity environment for those already undertaking the recommended weekly amount of physical activity. This topic is important for the design of health and wellbeing environments and interventions involving physical activity. Participants (N = 262) aged 18 to 71 years (M = 34.5, SD = 13.1) who met the UK physical activity guidelines completed the Nature Relatedness Scale, the trait section of the State Trait Inventory for Cognitive and Somatic Anxiety and the Psychological Well-Being Scale. Analysis via Multivariate ANOVA indicated that participants who engaged in outdoor physical activity reported significantly lower somatic anxiety levels and higher Nature Relatedness experience (NRexp). Significant results were not evident for wellbeing. Hierarchical regressions revealed that the psychological wellbeing facet of autonomy, NRexp, and outdoor physical activity predicted lower somatic anxiety, whereas indoor physical activity predicted higher somatic anxiety. Results indicate that somatic anxiety is lower for outdoor physical activity participation, and that outdoor activity, in conjunction with autonomy and NRexp, predicts lower anxiety levels. The findings extend previous work by demonstrating the impact of the physical activity environment on anxiety levels, as well as the contribution of outdoor physical activity and wellbeing facets to the previously established Nature Relatedness-anxiety relationship.